The science of monsters : the truth about zombies, witches, werewolves, vampires, and other legendary creatures - Hafdahl, Meg; Florence, Kelly (Skyhorse Publishing, 2019)
If you love film that scares, and want to believe that zombies, vampires, and other deadly and terrifying creatures could be real, let Meg Hafdahl and Kelly Florence, the women behind the Horror Rewind podcast called “the best horror film podcast out there” by Film Daddy, take you to the world where horror and science meet. How would a zombie really decompose in Night of the Living Dead? Are there instances of shape shifting in nature like in The Wolf Man? What is the science behind the night terrors that inspired the creation of Freddy Krueger? Is there scientific data supporting ghost detection like the tools used in Poltergeist? What is the psychological drive that compels cannibals like Hannibal Lecter? How does modern medicine and therapy differ from what would have been offered to Norman Bates in 1960? How are subliminal messages related to propaganda or brainwashing like in The Ring? What would the scientific explanation be for witches possessing people like in Carrie? Was The Blair Witch Project based on any real or imagined creature that came before?” And so much more! Gothic media moguls Meg Hafdahl and Kelly Florence revisit the films from their childhood to discover the science behind the fear. Join Kelly and Meg as they unravel the medical mysteries and scientific marvels that inspired the creation of famous monsters like Nosferatu, Norman Bates, Dracula, Frankenstein, and many more.